PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEAKTIFAN BELAJAR PADA MATA PELAJARAN PANCASILA UNTUK SISWA SEKOLAH DASAR - Yunita Ul Jannah; Nurdiansyah; Jennyta Caturiasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The lack of learning activeness in elementary school students in learning Pancasila education is the background of this research. Factors that are thought to affect the low activeness of student learning are due to students who lack self-confidence in learning activities in Pancasila education subjects. In the learning process, the activeness of students' learning is the main element that is very important in achieving learning goals. One thing that can be done to increase student learning activeness is to use the Problem Based Learning (PBL) model in Pancasila education subjects. This study aims to determine the effect of the Problem Based Learning (PBL) model on learning activeness in Pancasila education subjects for elementary school students. The research used quantitative research and the research method used was pre-experimental design type one group pretest-posttest (initial test single group final test). The subjects used in this study were 28 grade II elementary school students. This research instrument used a multiple choice test of 10 questions. The highest score on the pretest was 80 and the lowest score was 20, while on the posttest the highest score was 100 and the lowest score was 40. Based on the results of the study, it was concluded that the use of the Problem Based Learning learning model on learning activeness in Pancasila education subjects for elementary school students was 21.6%.